Elements of photogrametry with applications in GIS - Wolf, Paul R. ; Dewitt, Bon A. ; Wilkinson, Benjamin E. (McGraw-Hill Education, 2020)
Annotation: The definitive guide to photogrammetry--fully updatedThoroughly revised to cover the latest technological advances in the field, Elements of Photogrammetry with Applications in GIS, Fourth Edition, provides complete details on the foundational principles of photogrammetry as well as important advanced concepts. Significant changes in the instruments and procedures used in modern photogrammetry, including laser scanning, are discussed. Example problems clarify computational procedures and extensive photographs and diagrams illustrate the material presented in this comprehensive resource.Coverage includes:Principles of photography and imagingCameras and other imaging devicesImage measurements and refinementsObject space coordinate systemsVertical photographsStereoscopic viewingStereoscopic parallaxStereoscopic plotting instrumentsLaser scanning systemsElementary methods of planimetric mapping for GISTitled and oblique photographsIntroduction to analytical photogrammetryTopographic mapping and spatial data collectionFundamental principles of digital image processingPhotogrammetric applications in GISControl for aerial photogrammetryAerotriangulationProject planningTerrestrial and close-range photogrammetry